Retrograde metamorphism of ultrahigh-temperature granulites from the khondalite belt in Inner Mongolia, North China Craton: evidence from aluminous orthopyroxenes - Liu, Shoujie; Bai, Xiang; Li, Jianghai; Santosh, M. (Geological Journal, 2011)
Orthopyroxene-sillimanite-sapphirine-spinel-quartz granulites have been reported from the khondalite belt in Inner Mongolia. North China Craton (NCC), which record ultrahigh-temperature (UHT) metamorphism. These rocks record metamorphic temperatures up to 1050 degrees C and pressures up to 10 kbar during the peak metamorphism, as indicated by diagnostic UHT mineral assemblages such as equilibrium orthopyroxene + sillimanite + quartz, sapphirine + quartz and low-Zn-spinel + quartz. To well constrain the retrograde P-T conditions, we investigate orthopyroxenes in different textural settings in these UHT rocks and the results reveal marked variations in alumina contents, indicating a multistage formation. The core of coarse orthopyroxene porphyroblasts and some of the grains associated with sillimanite and quartz have the highest alumina content of up to 7.61-8.05 wt%. Rims of coarse orthopyroxene porphyroblasts and those occurring as coronas surrounding garnet grains have intermediate alumina value ranging from 6.21 to 7.61 wt%. Fine grained orthopyroxenes which form symplectite with cordierite have the lowest alumina content between 5.52 and 6.15 wt%. Based on the X(Al)-X(Mg) isopleths, orthopyroxenes in different textural associations and textures indicate formation under varying temperature and pressure conditions, ranging from 950 degrees C, 10.5 kbar to 840 degrees C, 8.5 kbar. These results are in accordance with the P-T estimates from previous studies on these rocks using Ti-in-zircon geothermometry and pseudosection analysis. The reaction textures and orthopyroxene chemistry suggest an initial stage of isobaric cooling followed by isothermal decompression, and a final stage of cooling. Combined with the available age data which suggest the timing of the UHT event as 1.92 Ga, and the previous models on P-T evolution of the khondalites, our results suggest a complex exhumation of the UHT granulites within the Inner Mongolia Suture Zone associated with the final assembly of the NCC within the Columbia supercontinent during the Palaeoproterozoic. Copyright (C) 2010 John Wiley & Sons, Ltd. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000289658400011&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 12 ARTICLE 2-3,SI 263-275 46